Worm-free sheep - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
A tropical breed of white hair sheep, St Croix, shows a remarkable immunity to intestinal worms. Within four to six weeks the lambs have developed almost complete resistance. Scientists at the Agricultural Research Service in Beltsville USA, have...